Charity School (Wolverhampton, England) records - Charity School (Wolverhampton, England)
Volume containing photocopies of orders and rules, minutes of the board of managers, financial records, and other material.
Photocopies.
Collection material in English.
Keywords: Charity-schools -- England -- Wolverhampton